Representation of Sexism in Philippa Lowthorpe’s Misbehaviour (2020) - Yusefa Laila Salma; Latifah Dwi Ariyani (Metaphor, 2024)
This research aims at analyzing the representation of sexism in Philipa Lowthorpe’s Misbehaviour (2020) and the society’s view towards women in the 1970’s in Philipa Lowthorpe’s Misbehaviour (2020). This research uses a descriptive qualitative method to analyze the film of Misbehaviour (2020) directed by Philipa Lowthorpe as the object research. The data collection methods include watching, reading, identifying, classifying, and selecting. The researcher utilizes Peter Glick and Susan T. Fiske’s theory of Ambivalent Sexism to analyze the data through steps of displaying, explaining, and interpreting. The result of this research shows that: the representation of sexism in in Philipa Lowthorpe’s Misbehaviour (2020) includes hostile sexism behaviors such as women inferiority and sexual objectification, and also benevolent sexism behaviors like paternalism, gender differentiation, and heterosexuality, the society’s view towards women in the 1970s that still restricted and narrow includes the way the society perceives women through the lens of Miss World beauty pageant, the persistence of gender stereotypes that reinforced traditional roles, the acknowledgment of the Women’s Liberation Movement, and the media representation of women during that period.